2010
DOI: 10.1111/j.1744-9987.2010.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Interleukin‐1 Receptor Antagonist by Combining a Leukocyte Adsorption Carrier With Ulinastatin

Abstract: Both granulocyte/monocyte adsorptive apheresis (GMA) and ulinastatin, a serine protease inhibitor, are reported to be effective in patients with ulcerative colitis; however, combination therapy with GMA and ulinastatin has not been attempted. Investigating the effect of ulinastatin on GMA is required for combination therapy since the inhibition of serine protease suppresses the reaction of GMA. To clarify the effects of ulinastatin on GMA, we investigated whether granulocyte adsorption to cellulose acetate bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Therefore, the reduction of TGF‐β release via CA beads might be due to this reduction of Th17‐cell differentiation, which may be one of the mechanisms of clinical efficacy of GMA in patients with IBD. Moreover, we also revealed that ulinastatin not only had the ability to increase the release of anti‐inflammatory cytokines, such as IL‐1ra and IL‐10 , but that it could also decrease TGF‐β release (Fig. ) in combination with GM and platelet adsorption to CA beads.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, the reduction of TGF‐β release via CA beads might be due to this reduction of Th17‐cell differentiation, which may be one of the mechanisms of clinical efficacy of GMA in patients with IBD. Moreover, we also revealed that ulinastatin not only had the ability to increase the release of anti‐inflammatory cytokines, such as IL‐1ra and IL‐10 , but that it could also decrease TGF‐β release (Fig. ) in combination with GM and platelet adsorption to CA beads.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have shown prevention of intestinal inflammation by IL‐10 in the gut, mainly by downregulation of the intestinal pro‐inflammatory Th1 response (15,16), suggesting that IL‐10 may play an important role as an immunoregulatory cytokine in the intestine also and that IL‐10‐rich conditions in colonic tissues may help to improve inflammation of the intestine. In this study, as a method to increase production of IL‐10, we investigated ulinastatin combined with GMA because ulinastatin increases production of IL‐1ra, an anti‐inflammatory cytokine, and M‐CSF with GM adsorption to CA beads (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…For IBD, it has been reported that intravenous injection of 200 000 units of ulinastatin weekly for 3 months in patients taking corticosteroids was effective in 64% of patients with moderate to severe UC who were resistant to steroid therapy (11), but ulinastatin has not been combined with GMA therapy. We have previously reported that ulinastatin, in combination with GM adsorption, increased the release of anti‐inflammatory cytokine IL‐1 receptor antagonist (IL‐1ra) in vitro (12), suggesting that administration of ulinastatin during GMA therapy may improve clinical efficacy in patients with IBD via the increase of IL‐1ra. Moreover, we have reported that ulinastatin administered with CA beads also increased M‐CSF production in peripheral blood (13).…”
mentioning
confidence: 99%
“…However, C5a, which is known as an activator of p38, ERK, and JNK in human monocytes [28], has been shown to be generated on CA beads [19,29,30]. Indeed, release of IL-1 receptor antagonist, which is induced by CA beads treatment, was partly inhibited by PD98059, an ERK inhibitor [31]. These findings allow us to speculate that the stimulation of C5a in the CA bead column might trigger TGF-b1 transcription by a mechanism similar to that controlling stimulation of the PS receptor.…”
Section: Foxp3 Induction By Ca Beadsmentioning
confidence: 95%